Pengaruh Media Pembelajaran Games Book Terhadap Minat Baca Siswa Pada Mata Pelajaran Bahasa Indonesia Kelas II SDN 14 Buwun Mas - Muh. Bisyrulhafy; Wawan Mulyadi Purnamab; Suhartini (Yayasan Azhar Amanaa Yogyakarta, 2026)
Reading interest is a fundamental literacy competency that should be developed in the early grades of elementary school because it supports students' learning and language development. However, students' reading interest remains relatively low due to limited use of engaging learning media. This study aimed to determine the effect of the game book learning media on the reading interest of second-grade students in Indonesian language learning at SDN 14 Buwun Mas during the 2025/2026 academic year. This research employed a quantitative pre-experimental design with a one-group pretest-posttest design. The participants consisted of 14 second-grade students selected through total sampling. Data were collected using reading tests, observations, and documentation, and analyzed using validity and reliability tests, the Shapiro-Wilk normality test, the paired-samples t-test, and the N-Gain Score, with the assistance of IBM SPSS Statistics version 25. The findings revealed an increase in the mean score from 67.86 on the pretest to 81.43 on the posttest, with an average improvement of 13.57 points. The paired-samples t-test yielded a p-value of 0.000 (p < 0.05), indicating that the use of the games book had a statistically significant effect on students' reading interest. Furthermore, the average N-Gain Score was 0.461 (46.13%), which falls into the moderate category, indicating that the learning media was reasonably effective in improving students' reading interest. These findings suggest that the games book can serve as an alternative instructional medium for creating more engaging, interactive, and student-centered literacy learning while supporting the development of sustainable reading habits in elementary schools.